Fiscal Devolution and Dependency - James Foreman-Peck; Laurian Lungu (Cardiff University, Cardiff Business School, 2005)
Public spending devolution in practice is widely seen as more appropriate for addressing varied political aspirations within state boundaries than is tax devolution. A drawback is that devolved public spending may be subject to irresistible upward pressure, as illustrated by 'formula drift' of the United Kingdom devolved administrations. By crowding out the private sector such public spending can exacerbate the problem it was originally intended to alleviate. When taxpayers do not value increases in government output at least as highly as the private goods and services they must forgo to finance them, then the public sector is too large. This paper estimates a three sector Hecksher-Ohlin model of the economy with the greatest relative rise of the public spending ratio in the United Kingdom, Wales. Simulation of the model shows a net gain in emp loyment from a one percent cut in income tax matched by a corresponding reduction in government spending. This result is consistent with the current level of intergovernmental transfers being excessive.
Keywords: R15; R58; 330; Fiscal Devolution; Small Open Economy Modelling; Crowding Out